Efficacy of Candida dubliniensis and Fungal β-Glucans in Inducing Trained Innate Immune Protection Against Inducers of Sepsis - Harriett, Amanda J.; Esher Righi, Shannon; Lilly, Elizabeth A.; Fidel, Paul; Noverr, Mairi C. (Frontiers in Cellular and Infection Microbiology, 2022)
Fungal-bacterial intra-abdominal infections (IAI) can lead to sepsis with significant morbidity and mortality. We have established a murine model of Candida albicans (Ca) and Staphylococcus aureus (Sa) IAI that results in acute lethal sepsis. Prior intraperitoneal or intravenous inoculation with low virulence Candida dubliniensis (Cd) confers high level protection against lethal Ca/Sa IAI and sepsis. Protection via Cd immunization is associated with decreased pro-inflammatory cytokines and mediated by Gr-1+ putative myeloid-derived suppressor cells (MDSCs) representing a novel form of trained innate immunity (TII). The objective of these studies was to determine the extent of Cd-mediated TII against sepsis of broad origin and explore the potential of fungal cell wall components as abiotic immunogen alternatives to induce TII, including zymosan depleted of TLR2 activity (d-zymosan), or purified preparations of β-glucan. Immunized mice were challenged 14 days post-immunization with a lethal array of live or abiotic inducers of sepsis, including Ca/Sa, Ca/Escherichia coli (Ca/Ec), LPS or untreated zymosan. Results showed that live Cd immunization was protective against sepsis induced by Ca/Ec and zymosan, but not LPS. Similar to protection against Ca/Sa, survival was dependent on Gr-1+ cells with no role for macrophages. Among the fungal cell wall compounds as immunogens, immunization with d-zymosan and an alkali-treated form of β-glucan also resulted in significant protection against sepsis induced by Ca/Sa or Ca/Ec, but not LPS sepsis. Again, there was a strong dependence on Gr-1+ cells for protection with one exception, an added role for macrophages in the case of protection induced by alkali-treated β-glucan. Overall, these results demonstrate that immunization with Cd as well as abiotic fungal cell components are capable of Gr-1+ cell-mediated trained innate immune protection against sepsis of broad microbial origin. In addition, abiotic β-glucans represent potential alternatives to live Cd for protection against lethal polymicrobial sepsis.